Knowledge, Institutions and Body experts. The case of the Third Pan American Congress of Physical Education, Uruguay 1950 - Dogliotti, Paola; Scharagrodsky, Pablo (Historia y Memoria de la Educación, 2022)
The following work analyzes, from a socio-historical perspective with emphasis on the social history of knowledge and experts, the III Pan American Congress of Physical Education held in Uruguay in 1950. The investigation focuses on the knowledge transmitted, the function of the experts and the role of institutions in the congress. Among the conclusions, three major issues are identified that strengthened the legitimacy and “scientificness” of the educational discipline, outlining certain types of intervention when educating and curing bodies in motion. One reinforced the relationship between physical education and education, another addressed various ways of conceptualizing “female” physical education, and another consolidated one of the great mandates of educational discipline: body measurement. In the circulation of these discourses, experts and institutions of sports and health played a fundamental role.